Seborrheic keratosis and insulin resistans - A. K. Aleksandrova; V. A. Smolynnikova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Regardless of multiple studies performed, aetiology and pathogenesis of seborrheic keratosis (SK) remain unknown. Insulin resistance may play the leading role. For instance, hyperinsulinemia is responsible for development of fibroepithelial polyps and acanthosis nigricans, diseases frequently associated with seborrheic keratosis. The purpose of the investigation is to study clinical factors and carbohydrate metabolism of patients with SK. Material and methods. The results of examination of 130 patients divided in two groups, were presented: 1st group with a single instance of SK (n = 60) and 2nd group with multiple SK (n = 70). All patients underwent histologic examination, analysis of carbohydrate metabolism: blood glucose, plasma insulin, level of glycated hemoglobin, glucose tolerance test; based on the results, advice from an endocrinologist was provided. Results and conclusions. Link between multiple SK and carbohydrate dysbolism was revealed: insulin resistance was found in 85.7% of patients from the 2nd group (16.6% in the 1st group). In our study, the association of multiple SK with fibroepithelial polyps and adiposity has evidenced that the patient suffered from type 2 diabetes mellitus.